Enhancement of Power System Transient Stability By Fractional Order Controlled STATCOM Tuned By PSO - Srinivas, R.S.; Rao, P.V.Ramana (International Journal of Engineering and Technology, 2018)
This paper discusses the application of Fractional order PI controlled Static synchronous compensator for improvement rotor angle stability of inter connected power system. FACTS Controllers plays important role in enhancing the power system stability.Besides improving the stability margin of the power system it also aids the damping of inter area power oscillations. In the present work STATCOM is connected in multimachine power system .The dynamic response of the STATCOM is controlled by using fractional order controllers.The controller gains of the fractional controller are tuned by using PSO algorithm.It gives acceptable solutions to continuous non-linear systems with less computational effort. The performance of the proposed controller has been compared with integer order PI controllers at different locations of fault. In this paper a 3 machine 9 bus WSSC test power system is considered and simulated in MATLAB/SIMULINK.